Differences in third metacarpal trabecular microarchitecture between the parasagittal groove and condyle at birth and in adult racehorses. (13th July 2018) - Anne‐Archard, N.; Martel, G.; Fogarty, U.; Richard, H.; Beauchamp, G.; Laverty, S.
Summary: Background: The aetiology of equine metacarpal condylar fractures is not completely understood and a developmental cause has been postulated. Objectives: To investigate the subchondral bone trabecular microarchitecture of the lateral parasagittal groove and condyle in equine neonates and its adaptation with maturation and athletic activity. Study design: Ex vivo observational study. Methods: Distal metacarpi of neonates, yearlings and adult racehorses (n = 24) were harvested. Dorsal and palmar frontal histological sections, containing the lateral parasagittal groove and condyle, were studied. The sections were digitalised and subchondral trabecular bone quantity and quality parameters and trabecular orientation in the frontal plane were measured. Results: Trabecular spacing and length were greater (P = 0.004 and P = 0.0005 respectively) whereas bone fraction, trabecular number and connectivity were all lower (P = 0.0004, P = 0.0001 and P = 0.001 respectively) in the lateral parasagittal groove compared with the condyle in neonatal foals. Trabecular thickness and bone fraction increased with age in racehorses and trabecular spacing decreased. The predominant trabecular orientation had a consistent pattern in neonates and it changed with maturity and the cumulative effect of racing at all the ROIs except for the palmar lateral parasagittal groove that retained a more 'immature' pattern. Main limitations: Samples were investigated in 2D. 3D processing could have provided more information. Conclusions: Already at birth there are striking differences in the subchondral bone trabecular microarchitecture between the lateral parasagittal groove and condyle in foals. Adaptation of trabeculae is confirmed with maturity in racehorses, with the greatest adaptation measured in bone quantity parameters. The trabecular orientation had a unique and more immature orientation pattern in the lateral palmar parasagittal grooves in adult racehorses and may reflect a weaker structure at this site.